Application of Artificial Intelligence in the Transformation of Digital Banking Systems: Opportunities, Challenges, and Future Outlook - Hameedullah Shuaa; Mohammad Aamer Mohammadi (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2026)
The swift progression of digital technologies has quite markedly reshaped the banking sector yet traditional banking infrastructures persist in grappling with hurdles in efficiency, customer engagement, and risk oversight. Artificial intelligence (AI) has surfaced as a pivotal facilitator in tackling these issues through process automation, bolstering decision-making, and offering tailored services. This investigation seeks to scrutinise the applications, opportunities, challenges, and prospective trajectories of AI within the metamorphosis of digital banking systems. A methodical literature review was undertaken, dissecting 23 peer-reviewed pieces issued from 2018 through 2025. The outcomes demonstrate that embracing AI enhances operational efficacy, client contentment, risk management, and adherence to regulations. What is more, ethical dilemmas, data privacy quandaries, algorithmic prejudice, regulatory ambiguities, and institutional preparedness indeed linger as substantial impediments. In sum, AI emerges as a strategic instrument adept at propelling innovation, competitive edge, and enduring expansion in digital banking for that matter, so long as entities confront implementation obstacles with due efficacy.